Awareness, susceptibility, and use of oral nicotine pouches and comparative risk perceptions with smokeless tobacco among young adults in the United States. - Meghan E Morean; Krysten W Bold; Danielle R Davis; Grace Kong; Suchitra Krishnan-Sarin; Deepa R Camenga (PLoS ONE, 2023)
Background Oral nicotine pouches (NPs) that contain nicotine but no tobacco leaves are rapidly gaining popularity. However, there is limited research on NPs, including within priority populations. In the current study, we examined awareness of, susceptibility to, and use of NPs in young adults as well as comparative risk perceptions with smokeless tobacco. Methods In 2021, 609 young adults (18-25 years) completed an online survey. Participants reported on NP awareness, susceptibility, and use as well as on comparative product perceptions for NPs versus smokeless tobacco. We ran unadjusted between-groups comparisons and an adjusted multinomial logistic regression to identify relationships between product perceptions and NP susceptibility and use. Results 41.5% of participants had heard of NPs before. Participants were non-susceptible (66.2%), susceptible (23.5%), or had used NPs (10.3%). Comparative product perceptions between NPs and smokeless tobacco suggested that young adults, as a whole, expressed uncertainty about the relative risk/benefit of using NPs versus smokeless tobacco. However, as expected, unadjusted and adjusted findings indicated that favorable perceptions of NPs versus smokeless tobacco were disproportionately observed among susceptible participants and NP users compared to non-susceptible individuals. Demographic differences were also observed (e.g., NP users were more likely than non-susceptible and susceptible individuals to have used smokeless tobacco). Conclusions Young adults reported awareness of, susceptibility to, and use of NPs, with findings indicating that favorable perceptions of NPs versus smokeless tobacco may contribute to NP susceptibility and use beyond known correlates like smokeless tobacco use. However, further research is needed to understand the full range of factors that are associated with NP susceptibility and use. It will be important to disentangle factors that are associated with potential positive public health impacts (e.g., switching from smokeless tobacco to exclusive NP use) from those associated with negative public health impacts (e.g., initiation among nicotine naïve individuals).